English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

1.
when ax + by = c, slope (gradient) is -a/b, so here it's -6/5.

2.
y = (1/3)x, so
(1/3)x = 2x + 10
(-5/3)x = 10
x = (-3/5)10 = -6
y = (1/3)(-6) = -2

2007-09-12 05:16:45 · answer #1 · answered by Philo 7 · 0 0

The y intercept is whilst x = 0. consequently -6(0) =5y=30. on account that -6(0) is 0, 5y=30 y = 6. The slope may be desperate by ability of making use of the x and y intercepts. interior the comparable way as above, the x intercept is whilst y = 0. consequently, -6x+0=30 which yields x=-5. good judgment dictates that y will strengthen by ability of 6 whilst x will strengthen by ability of 5, so the slope is 6/5. Stutch

2016-11-10 05:48:48 · answer #2 · answered by ? 4 · 0 0

Mr asta_la_vista:

1. gradient is the slope of the curve, so

6x + 5y = 30

5y = -6x + 30

y = -6/5 x + 6

slope = (-6/5); intercept = 6

2) substitute for y=1/3 x into the first equation
x/3 = 2x+ 10
multiply by 3 both sides of the equation,
x = 6x + 30

5x = -30
x= -6
y = x/3 = -6/3 = -2

And that's how is done. Good luck!

2007-09-12 05:16:55 · answer #3 · answered by alrivera_1 4 · 0 0

fedest.com, questions and answers